Imitation as a conjunction - Heyes, C (2008)
The conjunctive conception takes imitation to be a combination of observational learning and copying. In the target article, and elsewhere, this conception generates problems in (1) explaining the copying of intransitive actions, (2) elucidating the potential functions of imitation, and (3) recognising when the correspondence problem has been avoided rather than solved. Hurley's careful use of subpersonal and personal levels of explanation shows us how to tackle these and other questions about imitation. © 2008 Cambridge University Press.